Studi Perbandingan Alat Bukti Saksi dalam KUHAP dan KUHAP Islam - Aisyah, Aisyah; Azharuddin, Azharuddin; Rizal, Said; Zulkifli, Suhaila (Kajian Ilmiah Hukum dan Kenegaraan, 2022)
Purpose: of the study is to provide knowledge and comparative analysis of witness rules in the burgerlijk wetboek/civil procedural law in Indonesia and Islamic civil procedural law as well as to provide a comparison of witness arrangements in the burgerlijk wetboek/civil procedural law in Indonesia and the burgerlijk wetboek/Islamic civil procedure law. Result: Civil procedural law makes witnesses not perfect evidence. However, for the religious court in the case of divorce, the witness seems to have the same power as a letter, even thought in principle it is different. Contribution: This condition seems to make civil procedural law in the Islamic religious court the same as the law stipulated in the Quran&Hadith. Where as civil procedural law in Indonesia is the same between state and religious courts.